"바일 벡터"의 두 판 사이의 차이

수학노트
둘러보기로 가기 검색하러 가기
 
22번째 줄: 22번째 줄:
 
& = \frac{h^{\vee}-1}{2h^{\vee}}
 
& = \frac{h^{\vee}-1}{2h^{\vee}}
 
\end{aligned}
 
\end{aligned}
</math>$
+
</math>

2020년 11월 16일 (월) 04:24 기준 최신판

메모

\[ \begin{aligned} \omega_{\alpha}(\theta^{\vee}) & = \omega_{\alpha}(\sum_{\beta \in \Delta^+} n_{\beta}^{\vee} \beta^{\vee}) \\ & = n_{\alpha}^{\vee}, \end{aligned} \] \[ \begin{aligned} \langle \omega_{\alpha},\theta \rangle &= \omega_{\alpha}(\theta^{\dagger}) \\ & = \frac{\langle \theta,\theta \rangle}{2}\omega_{\alpha}(\theta^{\vee}) \\ & = \frac{\langle \theta,\theta \rangle}{2} n_{\alpha}^{\vee} \end{aligned} \]

  • 따라서

\[ \begin{aligned} \langle \rho,\theta \rangle & = \langle \sum_{\alpha\in \Delta^+} \omega_{\alpha},\theta \rangle \\ & = \sum_{\alpha\in \Delta^+} \frac{\langle \theta,\theta \rangle}{2} n_{\alpha}^{\vee} \\ & = \frac{h^{\vee}-1}{2h^{\vee}} \end{aligned} \]